Odpowiedzi

2010-04-14T21:16:48+02:00
2(x+3)=2x+6
5(3x-1)=15x-5
(-4) * (2a-b)=-8a+4b
-2(-4b+3)=8b-6
(a+b) * (-4)=-4a-4b
(4-5x+6y) * 3=12-15x+18y
-3(3x-2)=-9x+6
-1(3x-y+2)=-3x+y-2
2010-04-14T21:17:13+02:00
2(x+3)= 2x + 6
5(3x-1)= 15x - 5
(-4) * (2a-b)= -8a + 4b
-2(-4b+3)= 8b - 6
(a+b) * (-4)= -4a + -4b
(4-5x+6y) * 3= 12 - 15x + 18 y
-3(3x-2)= -9x + 6
-1(3x-y+2)= -3x + 1y - 2
2010-04-14T21:18:22+02:00
2(x+3) = 2x + 6
5(3x-1)= 15 x - 5
(-4)*(2a-b)= (-8)a + 4b
-2(-4b+3)= 8b - 6
(a+b)*(-4)= (-4)a - 4b
(4-5x+6y)*3= 12 - 15x + 18y
-3(3x-2)=-9x+6
-1(3x-y+2)=-3x+y-2